Cavity formation and its predictors in noncavitary nodular bronchiectatic Mycobacterium avium complex pulmonary disease. (April 2021) - Han, Dong-Woo; Jo, Kyung-Wook; Kim, Ock-Hwa; Shim, Tae Sun
Abstract: Introduction: The temporal dynamics of cavity formation in patients with the noncavitary nodular bronchiectatic (NC-NB) form of Mycobacterium avium complex pulmonary disease (MAC-PD) have not yet been well described. We aimed to investigate the development of new cavities in the NC-NB form of MAC-PD. Methods: Of the patients diagnosed with NC-NB-type MAC-PD between 2002 and 2013 and followed-up until July 2018 at a tertiary referral center in South Korea, we identified 589 patients who underwent follow-up chest computed tomography at least once after the diagnosis and retrospectively analysed their medical records. Results: The patients' mean age was 62.0 years, 64.7% were women. During the median follow-up of 3.8 years (interquartile range [IQR] 1.7–5.9), new cavity formation was noted in 51 (8.7%) patients. The median interval between the diagnosis of NC-NB MAC-PD and cavity formation was 3.7 years (IQR 1.8–5.4), with a constant occurrence over time. The Cox regression analysis showed that a history of pulmonary tuberculosis (adjusted hazard ratio [HR] 1.85; 95% confidence interval [CI] 1.06–3.23; P  = 0.030) and M. intracellulare as the causative organism (adjusted HR 2.03; 95% CI 1.15–3.59; P  = 0.014) were independently associated with new cavity formation. Conclusions: New cavity formation was noted in 8.7% of the patients with NC-NB MAC-PD in approximately 4 years after diagnosis, particular in those infected with M. intracellulare and those with a previous history of tuberculosis. Highlights: New cavity formation was noted in 8.7% of the NC-NB MAC-PD patients during follow-up period. The median interval between the diagnosis and cavity formation was 3.7 years. M. intracellulare and prior tuberculosis were predictors of cavity formation.